Peran Mahasiswa KKN 42 UIN-SU Medan dalam Pengembangan Potensi Ekonomi Masyarakat di Desa Karang Gading Kecamatan Labuhan Deli Kabupaten Deli Serdang - Zulfan, Willy; Ritonga, Hasnun Jauhari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Karang Gading village business owners are focused on the sustainability of their businesses. community development with social assistance methods to help with the problems being faced. The aim of Student KKN is more directed towards empowering the community with a pattern of managing existing village potential into economically valuable products, branding village potential through various assistance provided to the community regarding the utilization of local village potential which is rich in agricultural potential. This activity includes several steps, including outreach activities regarding the value of economic development through income potential in the village, product making training, practice in making processed products, KKN implementers and participants conducting evaluations and the Karang Gading Village community socializing processed products to their respective RTs as models. The community gave positive reactions to the initiatives that have been carried out. The community in particular wants events that can increase awareness of the value of the Village Economy. The community service event with the theme